A Research Synthesis of Unfocused Feedback Studies in the L2 Writing Classroom: Implications for Future Research - Barry Lee Reynolds; Chian-Wen Kao (National Research University Higher School of Economics, 2022)
Introduction. The issue of whether or not teachers should correct second language learners' grammatical errors has been hotly contested in the literature. Researchers who studied corrective feedback were particularly interested in determining what kinds of feedback may help students commit fewer errors in subsequent writing. One of the primary points of contention in this discussion is whether language teachers should provide focused (i.e., only one or a few types of grammar errors are targeted for correction) or unfocused written corrective feedback (i.e., all or most error types are corrected). Although focused feedback has been found to be more effective than unfocused feedback (Kao & Wible, 2014), focused feedback has been questioned to ecologically invalid in authentic classrooms (Xu, 2009). Because little attention has been paid to unfocused feedback effects, the present study looked into not only the short-term but also the long-term learning effects of unfocused feedback. Methods. The present study adopted the meta-analysis software Comprehensive Meta-analysis (Borenstein, Hedges, Higgins, & Rothstein, 2005) to calculate an effect size across previous studies. Several keywords were used to search for relevant studies in online databases and selection criteria were set to determine whether these studies were appropriate to be synthesized. 34 studies which met the criteria were included for analyses. Results and Discussion. This meta-analysis revealed that unfocused grammatical feedback was effective, as assessed by immediate posttests, and that the benefits of unfocused feedback increased over time, as revealed by delayed posttests, potentially contradicting Truscott's (1996; 2007) conclusions on grammar correction. This finding needs to be carefully interpreted because only 12 out of 34 studies provided statistical data in delayed posttests. Furthermore, publication bias seemed to be minimal, and both immediate and delayed posttest effect sizes were heterogeneous. Conclusion. It is strongly suggested that more future studies should investigate the long-term learning effects of unfocused feedback. In addition, because the effect sizes obtained for unfocused feedback practices were heterogeneous, other moderating variables need to be considered such as instructional settings (Mackey & Goo, 2007; Truscott, 2004a), type of feedback (Lee, 2013), focus of feedback (Ellis, 2009), learners' revisions (Ferris, 2010), intervention length (Li, 2010; Lyster & Saito, 2010) and so on. It is essential to conduct more meta-analyses to look into the potential effects of such moderating variables.